Acanthosis Nigricans: A Rare Presentation in a Patient with Hypothyroidism and Metabolic Syndrome - Rucha Sawant; Pranav Chaudhari; Sourya Acharya; Roma Chavhan (Journal of Clinical and Diagnostic Research)
A 38-year-old male came to the Medicine Outpatient Department (OPD) with complaints of easy fatigability for four months. He had no other significant history. Upon general examination, his Body Mass Index (BMI) was 33.2 kg/m2, and his waist circumference was 142 cm. The patient was diffusely hyperpigmented; upon examining his neck region, a dark, velvety hyperkeratotic plaque suggested Acanthosis Nigricans (AN) [Table/Fig-1].